An innovative approach to Raga pattern identification - Chakrabarty, Sudipta; Rai, Prativa; Islam, Md Ruhul; Deva Sarma, Hiren Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Raga is a fundamental element of Indian classical music (ICM), crucial for identifying the unique characteristics of a given song. Recognizing the embedded Raga allows for various applications, including music therapy, and leveraging the therapeutic effects of different Ragas. The use of mathematical techniques such as fast fourier transform (FFT) and fundamental frequency measurement (FFM) in calculating note values has proven effective for Raga pattern recognition. Both methods yield nearly identical results, facilitating accurate identification of Ragas. Once identified, these Ragas can be used for specific therapeutic purposes, harnessing their healing potential.